Cutting-edge research frontiers in oral cavity vaccines for respiratory diseases: a roadmap for scientific advancement - Sallard, Erwan; Aydin, Malik (Frontiers in Cellular and Infection Microbiology, 2024)
Intramuscular vaccines present limitations in eliciting robust mucosal immunity and preventing respiratory pathogens transmission. Sublingual vaccine administration offers promising advantages, including interconnected mucosal protection. Despite these advantages, only a few clinical trials have explored sublingual vaccines, underscoring the necessity of optimizing next-generation vaccine formulas. Critical research priorities include understanding vector behavior in the oral environment, understanding their interactions with mucosal immunity and developing formulations enabling sustained mucosal contact to facilitate efficient transduction. Consequently, tonsil organoids, as representative human mucosal models, could offer critical insights into sublingual immunization. Thus, a multi-disciplinary approach integrating pharmacological, immunological, and manufacturing considerations is pivotal for sublingual vaccines in targeting pathogen-aggravated prevalent respiratory diseases including asthma, COPD and lung cancer, as well as the antimicrobial resistance crisis.